The Transfer of Object Learning after Training with Multiple Exemplars - Baeck, Annelies; Maes, Karen; Meel, Chayenne Van; Op de Beeck, Hans P. (Frontiers in Psychology, 2016)
Object recognition improves with training. This training effect only partially generalizes to untrained images of the trained objects (new exemplars, orientation, …). The aim of this study is to investigate whether and to what extent the learning transfer improves when participants are trained with more exemplars of an object. Participants were trained to recognize two sets of stimuli using a backward masking paradigm. During training with the first set, only one exemplar of each object was presented. The second set was trained using four exemplars of each object. After three days of training, participants were tested on all the trained exemplars and a completely new exemplar of the same objects. In addition, recognition performance was compared to a set of completely new objects. For the objects of which four exemplars were used during training, participants showed more generalization towards new exemplars compared to when they were only trained with one exemplar. Part of the generalization effect extended to completely new objects. In conclusion, more variation during training leads to more generalization towards new visual stimuli.